2003
DOI: 10.1007/bf03179936
|View full text |Cite
|
Sign up to set email alerts
|

Growth factor releasing porous poly (ɛ-caprolactone)-chitosan matrices for enhanced bone regenerative rherapy

Abstract: Drug releasing porous poly(epsilon-caprolactone) (PCL)-chitosan matrices were fabricated for bone regenerative therapy. Porous matrices made of biodegradable polymers have been playing a crucial role as bone substitutes and as tissue-engineered scaffolds in bone regenerative therapy. The matrices provided mechanical support for the developing tissue and enhanced tissue formation by releasing active agent in controlled manner. Chitosan was employed to enhance hydrophilicity and biocompatibility of the PCL matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Chitosan has also been shown to induce specific effects on mucosal epithelia, namely the reduction of mucociliary clearance rates 15 and the relaxation of tight junctions 13 , 20 . These functions would facilitate an increased uptake of secondary adjuvants codelivered with chitosan as a solution or in a microparticulate form 21 , 22 , 23 , thereby reducing effective secondary adjuvant dose levels. In this study we demonstrated that this could be achieved not only with the known mucosal adjuvant CTB, but also with MDP, which has been shown to be, in general, poorly effective mucosally at low doses 54 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan has also been shown to induce specific effects on mucosal epithelia, namely the reduction of mucociliary clearance rates 15 and the relaxation of tight junctions 13 , 20 . These functions would facilitate an increased uptake of secondary adjuvants codelivered with chitosan as a solution or in a microparticulate form 21 , 22 , 23 , thereby reducing effective secondary adjuvant dose levels. In this study we demonstrated that this could be achieved not only with the known mucosal adjuvant CTB, but also with MDP, which has been shown to be, in general, poorly effective mucosally at low doses 54 .…”
Section: Discussionmentioning
confidence: 99%
“…At a molecular level this may result from highly specific translocation of tight junction proteins mediated by chitosan 20 . Moreover, chitosan can be formulated into particulate carriers with and without secondary polymers 21 , 22 , 23 , the subunit vaccine encapsulated or associated with the carrier, a process that is known to improve uptake by APC 24 . Chitosan‐based vaccines given mucosally have been shown to induce considerable, even protective, immunity to coformulated antigens, particularly of the humoral type 25 .…”
Section: Introductionmentioning
confidence: 99%
“…These systems allow control over the BMP release rate and promote pre-osteoblast differentiation and mineralization in vitro and ectopic bone formation in vivo [11,12]. Other growth factors involved in bone regeneration include FGF and PDGF, and a variety of materials have been used for their delivery [35,36].…”
Section: Bone Regenerationmentioning
confidence: 99%
“…Various modifications of chitosan scaffolds have been reported for their application as bone scaffolds and regeneration of bone tissue. Few of those studies include; platelet derived growth factor releasing porous PCL/chitosan matrices (Im et al 2003), poly(l-lactic acid) PLLA/chitosan hybrid scaffolds (Mano et al 2008), bone morphogenic proteins (BMP-2 and BMP-7), polymeric nanocapsules encapsulated fibrous chitosan scaffolds (Yilgor et al 2009), rhBMP-2-PLGA microspheres loaded chitosan/collagen scaffold (Shi et al 2009) (Wu et al 2010), PCL/chitosan scaffolds using melt stretching and multilayer deposition technique (Thuaksuban et al 2011), heparin functionalized chitosan scaffolds (Gümüşderelioğlu and Aday 2011), arginine-glycine-aspartic acid(RGD)-modified UV-crosslinked chitosan substrates (Tsai et al 2012). Bone is a complex tissue comprising of cells, organic and inorganic components, wherein the carbonated hydroxyapatite (HA) forms the major inorganic content.…”
Section: Chitosan Implants: Bonementioning
confidence: 99%